2021
DOI: 10.21037/hbsn-20-270
|View full text |Cite
|
Sign up to set email alerts
|

Liver tissue microbiota in nonalcoholic liver disease: a change in the paradigm of host-bacterial interactions

Abstract: Nonalcoholic fatty liver disease (NAFLD) pathogenesis is explained by the complex relationship among diet and lifestyle-predisposing factors, the genetic variance of the nuclear and mitochondrial genome, associated phenotypic traits, and the yet not fully explored interactions with epigenetic and other environmental factors, including the microbiome. Despite the wealth of knowledge gained from molecular and genome-wide investigations in patients with NAFLD, the precise mechanisms that explain the variability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
0
12
0
1
Order By: Relevance
“…Indeed, anatomically, the liver is a true receptacle for bacteria and derived products, filtering them from incoming blood through the hepatic artery and the portal vein. In a recent review [ 30 ], studies performed specifically in young people with MAFLD showed an increase in Prevotella copri , Proteabacteria and Escherichia species. Bacteria-derived products such as bacterial RNA and DNA can also induce host inflammatory responses by activating the innate immune defense system such as the inflammasome.…”
Section: General Information On Pediatric Mafldmentioning
confidence: 99%
“…Indeed, anatomically, the liver is a true receptacle for bacteria and derived products, filtering them from incoming blood through the hepatic artery and the portal vein. In a recent review [ 30 ], studies performed specifically in young people with MAFLD showed an increase in Prevotella copri , Proteabacteria and Escherichia species. Bacteria-derived products such as bacterial RNA and DNA can also induce host inflammatory responses by activating the innate immune defense system such as the inflammasome.…”
Section: General Information On Pediatric Mafldmentioning
confidence: 99%
“…In the case of visceral tissues previously considered sterile, it has been repeatedly shown that they contain microbial genetic material ( Aagaard et al, 2014 ; Ghaemi et al., 2021 ; Sookoian and Pirola, 2021 ). Indeed, hereby we could detect these from healthy arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, most of the internal organs and blood are considered sterile. However, recent evidence has challenged this dogma by molecular-based detection of microorganisms in different tissues of healthy and non-healthy individuals ( Paisse et al., 2016 ; Mansour et al., 2020 ; Molina et al., 2021 ; Sookoian and Pirola, 2021 ). Moreover, some authors could identify biologically relevant living microorganisms in these “sterile” regions ( Clifford and Hoffman, 2015 ; Potgieter et al., 2015 ; Moreno et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NAFLD and NASH are also more likely to have increased intestinal permeability via disruption of tight junction proteins that occurs after initial hepatic injury [35]. Interestingly, intestinal permeability through direct exposure of endotoxemia from lipopolysaccharide of gram negative microbes has also been suggested as playing role in the pathogenesis of NASH [36].…”
Section: Diseases With Associated Gut Barrier Disruption and Gut Dysb...mentioning
confidence: 99%